MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIKA DENGAN PENERAPAN STRATEGI RECIPROCAL TEACHING - Ranti Kurniasih (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2017)
The ability of mathematical connection is an important thing to be trained to students. Initial observation when this research was conducted showed that there were problems of mathematics learning in SMA Al-Muqoddasah of Ponorogo, that is, the tendency of teacher centered learning activities and low learning result of mathematics students especially in relation between some concepts in mathematics. Reciprocal Teaching Strategy is one of the alternatives that can be done to help students connect some concepts in learning mathematics, and enable students so that they can think creatively and critically. The purpose of this study is to describe the learning with Reciprocal Teaching strategy that can improve students' mathematical connection ability in SMA Al-Muqoddasah of Ponorogo. Keyword: Mathematical Representation Ability, Reciprocal Teaching.